Assessing technical efficiency of large and medium manufacturing industry in West Java Province, Indonesia: A data envelopment analysis approach - M. Mujiya Ulkhaq (The Eastasouth Management and Business, 2022)
Technical efficiency of Indonesian manufacturing industry has been measured in several studies. However, there is limited study conducted in large and medium manufacturing industries context. This study, therefore, aims to analyze the technical efficiency of the large and medium manufacturing industries in West Java Province, Indonesia. Understanding the technical efficiency is important as firms with full technical efficiency, the less inputs they use, the larger output they achieve. Data envelopment analysis with output-oriented and variable returns-to-scale is used to accomplish the objective of this study. The output is measured by total output value, while the inputs are cost of labor, raw materials, fuel, electricity, and gas, representation and royalty, fixed capital, as well as industrial service. Result shows that among twenty-four decision-making units under-investigated, nine of them are considered as the most efficient.